2018 European Frequency and Time Forum (EFTF) 2018
DOI: 10.1109/eftf.2018.8409010
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear enhancement of locking range of mutually injection-locked oscillators for resonant sensing applications

Abstract: Sensor architectures based on coupled resonators are receiving increased interest from the resonant sensing community. Certain output metrics of such sensors have an increased sensitivity to the measurand, compared to conventional resonant sensors with frequency-modulated outputs. In the present paper, we investigate the properties of a differential architecture based on mutually injection-locked oscillators beyond the linear theoretical framework, by driving the resonators higher than the critical Duffing amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…In this section, the dynamic properties of MILOs are illustrated: it is shown that their bandwidth is inversely commensurate with their sensitivity. We also show that the immunity of the amplitude ratio to the A-f effect reported in section III is limited to a narrow range of values of , close to = 0, irrespective of the increase of locking range resulting from nonlinear restoring forces [9], but depending on nonlinear damping forces. Finally, practical and fundamental limits of our analysis are discussed.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…In this section, the dynamic properties of MILOs are illustrated: it is shown that their bandwidth is inversely commensurate with their sensitivity. We also show that the immunity of the amplitude ratio to the A-f effect reported in section III is limited to a narrow range of values of , close to = 0, irrespective of the increase of locking range resulting from nonlinear restoring forces [9], but depending on nonlinear damping forces. Finally, practical and fundamental limits of our analysis are discussed.…”
Section: Discussionmentioning
confidence: 49%
“…In [17], the FOM of a MILO with nonlinear restoring forces and linear damping is computed for several values of . These simulations show that the linear increase of the FOM of with the oscillation amplitude is only valid within a narrow range of values of , commensurate with the linear locking range of the architecture, in spite of the nonlinear increase of the locking range with resulting from nonlinear restoring forces [9]. These results can be extended to the case when nonlinear damping is present in the system.…”
Section: V-b What ≈ Meansmentioning
confidence: 68%
See 3 more Smart Citations